2011
DOI: 10.1128/jb.00317-11
|View full text |Cite
|
Sign up to set email alerts
|

Antiparallel and Interlinked Control of Cellular Iron Levels by the Irr and RirA Regulators of Agrobacterium tumefaciens

Abstract: The plant pathogen Agrobacterium tumefaciens encodes predicted iron-responsive regulators, Irr and RirA, that function in several other bacteria to control the response to environmental iron levels. Deletion mutations of irr and rirA, alone and in combination, were evaluated for their impact on cellular iron response. Growth was severely diminished in the ⌬irr mutant under iron-limiting conditions, but reversed to wild-type levels in an ⌬irr ⌬rirA mutant. The level of uncomplexed iron in the ⌬irr mutant was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 72 publications
(105 reference statements)
7
80
1
1
Order By: Relevance
“…Previous studies in Bradyrhizobium japonicum, Rhizobium leguminosarum, A. tumefaciens and Rhodobacter sphaeroides demonstrated that transcription of the mbfA gene is regulated by iron levels, and is negatively controlled by the iron response regulator (irr) under ironlimiting conditions (Hibbing & Fuqua, 2011;Peuser et al, 2012;Ruangkiattikul et al, 2012;Rudolph et al, 2006;Todd et al, 2006). It has been shown that the expression of A. tumefaciens mbfA is also inducible upon exposure to H 2 O 2 and MbfA plays a role in H 2 O 2 resistance, possibly by removing intracellular free iron and thus preventing the Fenton reaction (Ruangkiattikul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Bradyrhizobium japonicum, Rhizobium leguminosarum, A. tumefaciens and Rhodobacter sphaeroides demonstrated that transcription of the mbfA gene is regulated by iron levels, and is negatively controlled by the iron response regulator (irr) under ironlimiting conditions (Hibbing & Fuqua, 2011;Peuser et al, 2012;Ruangkiattikul et al, 2012;Rudolph et al, 2006;Todd et al, 2006). It has been shown that the expression of A. tumefaciens mbfA is also inducible upon exposure to H 2 O 2 and MbfA plays a role in H 2 O 2 resistance, possibly by removing intracellular free iron and thus preventing the Fenton reaction (Ruangkiattikul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Irr and RirA are regulators of the suf operon (Hibbing & Fuqua, 2011;Todd et al, 2006). The Fe-S containing the RirA form may be used as a reporter for sensing cellular Fe-S status and controlling synthesis via the suf operon in response to changing demands for Fe-S clusters.…”
Section: Discussionmentioning
confidence: 99%
“…3). Irr and RirA are involved in iron regulation (Hibbing & Fuqua, 2011;Todd et al, 2006) and also in the induction of the suf operon by oxidative stress (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations